Peran Disiplin Mata Kuliah Ilmu Filfasat dalam Strategi Pendidikan untuk Mahasiswa Bidang Ilmu Administrasi Publik - Hendri Suwarsono (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to identify the optimal model in the integration of philosophical disciplines in the structure of the educational program of “Public Administration” students, as well as explore the features of the management of educational strategies suitable for the training of civil servants. The main focus of this research is: 1) academic management strategies to overcome curriculum overlap due to the dominance of philosophical disciplines in public administration study programs; 2) adaptation of educational programs for public administration students to be in line with the needs of the world of work, both at national and international levels; 3) characteristics of internationalization of public administration education programs, especially in the context of academic mobility and adaptation of the Indonesian public administration system to global standards. This research uses the cultural-historical analysis approach, comparative method, structural-functional method, and expert evaluation to explore and analyze problems and develop solutions. The research findings show that the dominance of traditional philosophy courses in the curriculum is often ineffective in shaping the competencies needed in the world of work. The research identified three main challenges: saturation of the curriculum with theoretical courses, lack of connection between the curriculum and the practical needs of the working world, and low use of English in teaching key courses. To address these issues, this research proposes restructuring the curriculum through the integration of three disciplinary groups: applied logic, cultural studies, and applied political science. In addition, the implementation of a contextualized bilingual learning model is also considered as a solution to improve the relevance of the curriculum. The uniqueness of this article lies in its approach that combines philosophical studies with managerial strategies in curriculum design, complemented by empirical experiences from international and cross-institutional cooperation. This article offers a reinterpretation of the utilization of philosophy as a tool for the development of professional competence in public administration education, not just as an abstract worldview.